Pengaruh Lingkungan Belajar, Disiplin Belajar, Motivasi Belajar terhadap Hasil Belajar pada Tahfiz di SMKN 1 Sungai Aur - Irja Eka Putri; Ulva Rahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to examine the impact of learning atmosphere, perseverance in learning, and learning motivation on the Tahfiz achievement of students at SMKN 1 Sungai Aur. The method used in this study is quantitative with a causal associative design. The population studied includes all students from grades X, XI, and XII at SMKN 1 Sungai Aur using proportional random sampling. Data were collected through the use of closed questionnaires for the variables of learning atmosphere, perseverance in learning, and learning motivation, as well as documentation of Tahfiz scores as an indicator of learning achievement. Data analysis included validity and reliability testing, classical assumption testing, and multiple linear regression analysis. The research findings show that learning atmosphere, perseverance in learning, and learning motivation together have a significant effect on Tahfiz learning achievement. Individually, the three independent variables also have a significant impact, with learning motivation being the most influential variable. This study emphasizes the importance of creating a supportive learning atmosphere, cultivating perseverance in learning, and strengthening spiritual motivation to improve the quality of Tahfiz learning.